Analyzing the 7Ps of Marketing Services of Organic Agricultural Stores in Bang Bua Thong District - Thriyawanich, Chalita; Ayasanond, Chitpong; Munkongtum, Chutidaj (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: This research focuses on the marketing services of organic agricultural stores, aiming to understand the demographic characteristics, purchasing behaviors, and customer satisfaction towards the 7P marketing strategy. This is a growing and high-potential market in Thailand. The objectives are to (1) explore the demographic and personal characteristics of customers, (2) study the purchasing behaviors and decision-making of customers, and (3) analyze customer opinions and satisfaction towards the 7P marketing strategy. This research provides deeper insights into customer needs and expectations in the organic agricultural market and suggests effective marketing strategies to compete in a highly competitive market. Methodology: This quantitative research used statistical data analysis to understand the 7P marketing strategy of organic agricultural stores in Bang Bua Thong district. The primary subjects were customers of these stores, with a sample size of 385 determined using Cochran's formula and a purposive sampling method. Questionnaires were the main tool, validated for appropriateness and reliability using IOC = 0.67 and Cronbach's Alpha = 0.72. Both online and paper questionnaires were utilized. Data were managed and analyzed using statistical software, employing basic statistics for objectives 1 and 2, and inferential statistics for objective 3. Results: The research found that most customers are females aged 31-40 years with bachelor's degrees, employed in private companies. Their purchasing behavior mainly focuses on rice and vegetables from supermarkets and fresh markets, with an average expenditure of 501-1,500 baht per transaction. The product quality and pricing strategies received the highest satisfaction scores, while promotion strategies scored the lowest, indicating a need for improvement in this area. Conclusion: The research in Bang Bua Thong district on the 7P marketing strategy of organic agricultural stores reveals that product quality, price, location, and personnel significantly affect customer satisfaction, while promotional activities require further development. These findings guide the improvement of marketing strategies to enhance customer satisfaction and loyalty.